Prognostic significance of retention index of bone marrow on dual-phase 18F-fluorodeoxyglucose positron emission tomography/computed tomography in patients with diffuse large B-cell lymphoma. Issue 2 (January 2018) - Chang, Chin-Chuan; Cho, Shih-Feng; Chuang, Ya-Wen; Lin, Chia-Yang; Huang, Ying-Fong; Tyan, Yu-Chang
Abstract : Abstract: The purpose of this study was to determine the prognostic significance of F-18 fluorodeoxyglucose (FDG) uptake on a dual-phase positron emission tomography/computed tomography (PET/CT), focusing on the increment in maximal standardized uptake value (SUVinc) of tumor and bone marrow (BM) between initial and delayed phase images and retention index (RI) of tumor and BM, in patients with diffuse large B-cell lymphoma (DLBCL). From September 2009 to January 2013, 70 patients (37 males and 33 females, aged 60.6 ± 17.5 years) with DLBCL who had undergone dual-phase FDG PET/CT scans for pretreatment staging were enrolled. The patients subsequently received combination chemotherapy with rituximab. The dual-phase SUV, including SUVinc of tumor (SUVinc-t), RI of tumor (RI-t), SUVinc of BM, and RI of BM were measured. The clinical observation period was from September 2009 to December 2014. Both univariate and multivariate analyses were then used to assess the prognostic significance of SUVinc, RI, international prognostic index (IPI), gender, age, clinical stage, and laboratory tests. The median follow-up time was 35.5 months. The 3-year overall survival (OS) for patients with low/high SUVinc-t (cut-off 2.0) and for patients with low/high RI-t (cut-off 20) were 87.5%/ 62.1% ( P = .08) and 83.3%/ 62.7% ( P = .14), respectively. The 3-year OS for patients with SUVinc-i < 0.35 and for those with SUVinc-i ≥ 0.35 were 73.2% and 53.3%, respectively ( P = .10). The 3-year OS for patients with RI-i < 45 and for those with RI-i ≥ 45 were 72.7% and 37.5%, respectively ( P = .02). Subsequently, the Cox multivariate forward proportional hazards model revealed that a higher RI-i (hazard ratio: 4.49; 95% confidence interval: 1.64–12.32; P = .0035) and IPI were independent prognostic factors affecting OS. For patients with DLBCL, an elevated RI-i (≥45) was a predictor for shorter OS, independent of IPI score. It added to the value of pretreatment dual-phase FDG PET/CT scans. Abstract : Supplemental Digital Content is available in the text